Prognostic value of adjuvant chemotherapy for hormone receptor-negative T1a and T1bN0M0 breast cancer patients - Yaxiong Liu; Honghui Li; Jinsong Li; Changlong Wei; Jinsheng Zeng; Qiuhong Tian (Scientific Reports)
Abstract The benefit of adjuvant chemotherapy (CT) for hormone receptor-negative T1a and T1bN0M0 breast cancer remains uncertain. Our study was to explore prognostic value and identify candidates of adjuvant CT for these patients. The data of hormone receptor-negative T1a and T1bN0M0 breast cancer patients were extracted from the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015. All patients were divided into two groups according to the history of adjuvant CT namely the CT group and the no CT (No CT) group. Univariate and multivariate Cox regression analysis were utilized to identify factors linked with cancer specific survival (CSS) and overall survival (OS) for the patients. Kaplan-Meier method was employed to determine survival benefit of adjuvant CT. A total of 3889 patients were included. After propensity score-matching, 1217 patients were assigned to the CT group and 1217 patients were assigned to the No CT group respectively. Based on multivariate Cox regression analysis of OS, older age, single, T1b stage, triple-negative tumor and absence of adjuvant CT were identified as risk factors related to OS. Besides, multivariable Cox regression analysis of CSS showed significant association between grade III+IV, T1b stage, triple-negative tumor and absence of adjuvant CT and CSS. The results from Kaplan-Meier curves revealed that adjuvant CT could bring OS benefit for these patients with more than two risk factors and could improve CSS for the patients with more than one risk factor. Our study supports the implementation of individualized strategies for hormone receptor-negative T1a and T1bN0M0 breast cancer patients. Adjuvant CT was recommended for potential beneficial patients after undertaking a risk-benefit discussion.